Effect of transcutaneous electrical acupoint stimulation on pregnancy outcomes in women with in vitro fertilization-embryo transfer: A systematic review and meta-analysis - Zhu, Fengya; Zhao, Bo; Wu, Jie; Yin, Shao; Ma, Tingting; Li, Zimeng; Zhu, Xinyun; Wang, Tianyu; Yang, Bin; Che, Deya (Frontiers in Cell and Developmental Biology, 2022)
Objective: The purpose of this systematic review and meta-analysis was to evaluate the efficacy and safety of transcutaneous electrical acupoint stimulation (TEAS) on pregnancy outcomes in women undergoing in vitro fertilization-embryo transfer (IVF-ET), in order to provide evidence-based medical support. Methods: We searched the Cochrane Library, Embase, PubMed, Web of Science, SinoMed, and CNKI for relevant randomized controlled trials (RCTs) from inception to May 31, 2022 using the search terms “transcutaneous electrical acupoint stimulation,” “TEAS,” “in vitro fertilization-embryo transfer,” “IVF-ET,” “randomized controlled trial,” and “clinical trials.” The experimental group was treated with TEAS or combined with ovulation-inducing medication, and the control group was treated with mock TEAS (mTEAS), ovulation-inducing medication, or no intervention. The main outcome was the clinical pregnancy rate. Secondary outcomes were the embryo implantation rate, live birth rate, biochemical pregnancy rate, number of oocytes retrieved, and number of adverse events. Stata15.1 software was used for data summary and analysis. Results: This review involved 15 RCTs and 4,281 participants. TEAS were superior to the control group for improving the clinical pregnancy rate [RR: 1.29, 95% CI: 1.19 to 1.40; P < 0.001; I2 = 23.0%], embryo implantation rate [RR: 1.43, 95% CI: 1.22 to 1.69; P < 0.001; I2 = 35.9%], live birth rate [RR: 1.33, 95% CI: 1.14 to 1.54; P < 0.001; I2 = 47.3%], and biochemical pregnancy rate [RR: 1.15, 95% CI: 1.05 to 1.26; P = 0.003; I2 = 49.1%], without significant heterogeneity.We performed subgroup analysis based on the sample size and interventions. The results showed that the sample size had no effect on the results. There was no significant difference between TEAS and ovulation-inducing medication in the clinical pregnancy rate or the embryo implantation rate. In addition, TEAS did not significantly increase the embryo implantation rate or the live birth rate, compared with no intervention. In terms of safety, mild allergic symptoms were found in both the experimental group and the control group. Conclusion: In general, existing evidence supports the potential value of TEAS as an adjunctive treatment for improving pregnancy outcomes. High-quality, large-sample RCTs are needed to further support this conclusion.